Fixed Ideas and Ideologies: Developing a New Epistemology Rooted in Apathy - Isrow, Zachary (Conatus - Journal of Philosophy, 2024)
Epistemologies are overwhelmingly riddled with biases, influenced by ideologies and fixed ideas. Max Stirner and Louis Althusser argue at length regarding the negative impact of these on our way of thinking. This paper argues that the only escape from Stirner’s fixed ideas or Althusser’s ISAs (Ideological State Apparatuses) is through an apathetic disposition to the truth – something very unphilosophical in nature. In order to create parallactic shifts in thought, we must also develop a new epistemology, one rooted in apathy. Through this, we can become true philosophers and thinkers moving towards a truth not solely determined by our pre-held assumptions.